Differential production of intracellular gamma interferon in alpha beta and gamma delta T-cell subpopulations in response to peritonitis. - Berguer, R (1995)
Flow cytometry was used to measure T-cell intracellular gamma interferon and surface interleukin 2 re-ceptor expression in response to peritonitis in rats. Interleukin 2 receptor expression levels were similar in the two T-cell subsets, but gamma interferon production was increased fivefold in gamma delta T cells compared with pro-duction in alpha beta T cells. Our results provide further evidence of an early and vigorous gamma delta T-cell response to bac-terial infection.